Convalescent Plasma Coupled With Medications for the Treatment of a Severe COVID-19 Patient: Drugs Analysis and Pharmaceutical Care Based on the Newly Established Guidelines for COVID-19 Remedy - Wang, Ying; Zhang, Yang; Yu, Qian; Zhu, Kun (Frontiers in Pharmacology, 2020)
Given the extreme importance of the current pandemic caused by COVID-19 and due to the fact that scientists agree that there is no identified treatment, this paper analyzes in detail the treatment of a severe COVID-19 patient with convalescent plasma and drugs based on current guidelines for COVID-19 diagnosis and treatment. This can provide a reference for other medical institutions on rational drug use and pharmaceutical care for severe COVID-19 patients.